PERTANGGUNGJAWABAN HUKUM KORPORASI TERHADAP PETI DALAM PERSPEKTIF HUKUM BISNIS DAN ESG - Jessica Claudia, Sijabat (Ensiklopedia Sosial Review, 2025)
Unlicensed Gold Mining (PETI) represents a complex legal and environmental issue within Indonesia’s mining sector, generating significant challenges for environmental protection and legal governance. This study aims to analyze the form of corporate legal liability for involvement in PETI through a case study of Ketapang District Court Decision No. 332/Pid.Sus/2024/PN.Ktp, and to assess its conformity with Law No. 4 of 2009 on Mineral and Coal Mining as amended by Law No. 2 of 2025 and Government Regulation No. 39 of 2025. The research employs a normative juridical method using both statute and case approaches. The findings indicate that enforcement of corporate liability remains weak, as legal actions tend to focus on individual perpetrators. Furthermore, the integration of Environmental, Social, and Governance (ESG) principles into judicial considerations is still limited. Based on Gustav Radburch’s Theory of Legal Certainty, this decision provides formal legal certainty for the state but does not yet fully achieve substantitve justice or legal utility. The study recommends strengthening legal instruments and policy frameworks to embed ESG principles and the value of legal certainty into corporate accountability mechanisms, thereby promoting fair, sustainable, and responsible mining governance. Keywords: Corporate Legal Liability, Unlicensed Gold Mining, ESG, Legal Certainty, Law Enforcement